Can high and volatile prices be good for the poor? - Andrea Guariso; Mara P. Squicciarini; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
For decades, despite widespread hunger and severe malnutrition in developing countries there was little attention to agricultural development and food security, and global funding for it was declining. High and volatile food prices have caused a dramatic turnaround in public and political attention to agriculture and food security issues and raised public aid and private funding for it, while global malnutrition has not increased and poverty declined over the past years. Mass media played a crucial role. Policy makers' priorities, global policy agendas and donor funding have followed. Hence, besides a major challenge, the food price spikes also have created a unique opportunity to address poverty and hunger.
Keywords: 330